Classification of blasts in acute leukemia blood samples using k-nearest neighbour - Nadiatun Zawiyah, Supardi; Mohd Yusoff, Mashor, Prof. Madya Dr.; Nor Hazlyna, Harun; Fatimatul Anis, Bakri; Rosline, Hassan, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/